ESSENTIAL MICRONUTRIENTS – COMPONENTS OF ANTIOXIDANT PROTECTION IN SOME SPECIES ALLIUM - T. I. Shirshova; I. V. Beshley; N. A. Golubkina; F. V. Golubev; E. V. Kljuykov; V. A. Cheryomushkina (Овощи России, 2019)
One of the urgent tasks at the present time is to obtain and widely use functional foods that have antioxidant  and anticarcinogenic effects, which serve not only to meet human needs  in   proteins,  fats,  carbohydrates, micro  -   and macronutrients,  but also contribute to the immune system, improve the heart and other human organs. For food plants, rich in antioxidant protection components, include perennial onions, from the variety of wild species which are in demand by modern medicine are only very few. The Republic of Komi is classified as the most uncomfortable  territories for human habitation.  In the flora of the Komi Republic there are three types of perennial bows – Allium angulosum  L., A. schoenoprasum L. and A. strictum Schrad.   The collection of the Botanical garden of the Institute of biology, Komi scientific center includes more than 150 species. Comparison of the chemical composition of  four  types  of  onions  from  the Botanical gardens of the Komi scientific center and Moscow state University (MSU) showed that  the  total  content  of flavonoids in  onions, Komi scientific center of  the  BS  is much higher, and the content of selenium is lower than in the same types of BS, Moscow state University. In samples of onions sticking out in the Republic of Tuva, the Republic of Buryatia,  in the Altai Mountains, the Se content is also much higher than in regional species. The soils of the Komi Republic are  depleted  Se,  however, as  shown  by  our research, wild and cultivated species of the genus Allium, are batteries of this trace element. According to our calculations, the use of 100 g of fresh herbs of chives may meet up to 60% of the daily needs of the human body in ascorbic acid, up to 94% manganese, 20% copper, 12% zinc.